Preparation of Optical Window in the Infrared Region (35) µm Using Al2O3 Material - Iltaif, A.K.; Al-Hilli, B.A.; Abbas, L.N.; Hasan, S.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work optical window for infrared region was prepared by using Aluminum Oxide (Al2O3)material as antireflection coating on ZnSe substrate which covers the atmospheric window 3-5µm. the maximum transition was 97% at a wavelength 0f 4.4µm.